Decontamination of methyl parathion in activated nucleophilic systems based on carbamide peroxisolvate - Vakhitova, Lubov; Bessarabov, Volodymyr; Taran, Nadezhda; Kuzmina, Galina; Zagoriy, Glib; Baula, Olga; Popov, Anatolii (Eastern-European Journal of Enterprise Technologies, 2017)
The study has specified the nucleophilic decomposition of methyl parathion (O,O-dimethyl-O-(4-nitrophenyl) thiophosphate) by an НОО– anion generated from carbamide peroxysolvate in the presence of ammonium bicarbonate and boric acid. The revealed effect is the supernucleophilic reactivity of the diatheroxoborate anion ( ) ( )− 2 2 B OH OOH , which is two orders of magnitude higher than the analogous value for the НОО– anion. The tests have shown the principle possibility of using solid sources of hydrogen peroxide in degassing nucleophilic systems. The value of the α-effect ( − − HOOHOk k ) has been determined, which indicates an abnormally high reactivity of the HOO– anion in the decomposition of toxic phosphorus compounds. The obtained data show that the activation of hydrogen peroxide with ammonium bicarbonate and boric acid can be considered as a new approach to the creation of soft ecological systems of decontamination of nucleophilic and oxidative effects. The results obtained can be used to develop long-term decontamination systems for decomposing highly toxic pesticides and active pharmaceutical ingredients of organophosphorus nature. Such systems can be used to eliminate the consequences of contamination with components of chemical weapons, toxic pesticides, and toxic active pharmaceutical ingredients.